Handbook of Non-Ferrous Metal Powders Technologies and Applications. - Neikov, Oleg (Elsevier, 2009)
A heavyweight classic from the Ukraine and Russia: everything on non-ferrous metal powders.
Keywords: Powder metallurgy -- Handbooks, manuals, etc.; Nonferrous metals -- Handbooks, manuals, etc.; elektronické knihy; electronic books